The Effect of Celebrity Endorsers and Green Perceived Value on Purchase Behavior Mediated by Green Trust Variables - Puspadewi, Mellania Indah; Sugandini, Dyah (Southeast Asian Business Review, 2024)
Celebrity endorsers are an important part of a product's promotional strategy and marketing campaign. The hope is that the image or quality of the celebrity will be transferred to the product and stimulate sales to increase the Purchase Behavior of consumers. The purpose of this study is to determine the effect of celebrity endorsers and green perceived value on purchase behavior mediated by the green trust by consumers at Easy Peasy Salad Bar & Healthy Catering. The method used in this study was causative correlational research involving 175 samples. The questionnaire became an instrument in this study using 19 indicators from each variable. The results of this study show the influence of Celebrity Endorsers and Green Perceived Value positively and significantly; Green trust is directly stated to have an influence and significance in mediating the influence of Celebrity Endorsers and Green Perceived Value on Purchase Behavior, as well as green trust have a positive and significant influence on Purchase Behavior in consumers at Easy Peasy Salad Bar &; Healthy Catering.